The potential use of humic acid-coated biochar for reducing Pb and Cu in the soil to improve plant growth - Amir Hamzah; Rossyda Priyadarshini; Astuti Astuti (Brawijaya University, 2022)
The use of biochar for remediating heavy metal-polluted soils is still partial. Various methods of controlling soil pollution are currently being implemented by combining several methods. One of which is coating the biochar with humic acid to increase the effectiveness of nutrient uptake by plants. This study aimed to elucidate the effect of humic acid-coated biochar (HCB) on reducing Pb and Cu in the soil to improve plant growth. Treatments tested were combinations of two factors. The first factor was the dose of HCB, namely D0 = control (without HCB), D1 = 15 t HCB ha-1, D2 = 30 t HCB ha-1, and D3 = 45 t HCB ha-1. The second factor was the type of plants, namely spinach (P1), water spinach (P2) and mustard green (P3). Twelve treatments were arranged in a randomised block design with three replications. The parameters observed were plant height, plant leaf area, plant stem diameter, and plant fresh weight. The results showed that the best plant growth was achieved at a dose of 30 t HCB ha-1. The mustard green had the highest Pb uptake (0.025 g pot-1), and the lowest Pb uptake (0.014 g pot-1) was observed for water spinach. The highest Cu uptake (0.443 g pot-1) was observed in water spinach, followed by spinach (0.282 g pot-1) and mustard green (0.143 g pot-1). In general, the amount of Pb reduced by plants ranged from 40.04 to 87.28%, and the amount of Cu by plants ranged from 8.63 to 40.23%.